Penentuan Komoditas Unggulan Perikanan Laut Pelabuhan Perikanan Cirebon dan Peranannya Dalam Pembangunan Ekonomi Wilayah - Andi Perdana Gumilang; Evi Susilawati (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2020)
Cirebon region which has a fishing port as a landing place for catches has a strategic role in fisheries economic development. However, the role and potential are still not optimized properly. The purpose of this study was to analyze the role of the fisheries subsector in the economic development of commodity-based catches at the port of Kejawanan fishery which is the largest fishing port in Cirebon. The analytical tool used in this study is the Location Quotient (LQ) analysis. The results showed that the capture fisheries commodities in the fishing port that were the main seeds were squid, stingray, gliding, tetengkek, cob, gray, Kuwe, Japuh, Alu-Alu, Jackfruit seeds, Cleaver-machete, and Talang. This is because it has a positive LQ growth value with a score of 3. The LQ score of 3 indicates that these fish species are relatively concentrated landing at the port of fishing and can continue to be developed with sustainable fisheries management to encourage regional economic growth. The role of the Cirebon fisheries sub-sector is a base sector with a LQ value of 3.02.